Regional Economic Outlook, May 2009, Asia and Pacific : Global Crisis: The Asian Context. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2009)
Asia has been hard hit by the global financial crisis. Despite strong fundamentals, its pervasive linkages to the rest of the world have exposed it to the collapse of demand and credit in advanced countries. Exports and industrial production have fallen sharply, capital has started to flow out of the region, and leading indicators suggest further weakness ahead. Against this background, the May 2009 APD REO will discuss the latest developments in Asia, examine the prospects for the period ahead, and consider the policy steps needed to revive economic activity and restore corporate and financial sector health.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet